Estudio de factibilidad para la instalación de una sucursal de la empresa impresión publicitaria en el cantón Buena Fe, provincia de Los Ríos, año 2012 - Oña Villalva, Jessica Soraya (2012)
It is considered that a project approach is a solution to a problem that tends to resolve among many things, some need of man, from this perspective investment projects are described as a plan if assigned certain amount of capital and provides inputs of various types may produce a good or a service useful to human beings or society as a whole. Currently a smart investment required to justify a base, this base is just a project well structured and evaluated to indicate the process to be followed and there is where is the need to evaluate projects. The current project named Feasibility Study for the establishment of a branch Flyer Printing Company in Buena Fe Canton province of Los Ríos Year 2012, born as a business idea, considering the needs identified in the Canton Good Faith, the same despite being a thriving commercial sector does not own an advertising company to meet the needs of entrepreneurs in the field of development of billboards. The project became known that people who own businesses and want to get billboards, pay very high prices as the only two advertising companies which owns Buena Fe, only act as intermediaries, is get an advertising contract and come up Quevedo city for making signs, situation which requires the customer to pay a cost of resale. With the installation of the Branch Company Advertising Print Advertising is obtained, time optimization, better quality, and low price, thus contributing to the socioeconomic development of the county in good faith and its citizens.